2002
DOI: 10.1161/01.str.0000023888.43488.10
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Short-Term Outcome of Cerebral Infarction in Young Adults in Western Norway

Abstract: Background and Purpose-We sought to determine the incidence and short-term outcome of people aged 15 to 49 years with first-ever cerebral infarction in 1988 -1997 in Hordaland County, Norway. Methods-Cases were found from computer search of hospital registries and detailed review of patient records. Stroke subtype was classified according to the major intracranial artery affected. Short-term outcome was evaluated by the modified Rankin Scale (mRS). Results-A total of 96 women and 136 men met the inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
69
4
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 15 publications
13
69
4
8
Order By: Relevance
“…3,6,15,16 The first-year mortality rates varied from 4.5% to 6.3%, 2,5-7 and the average rates were between 0.8% and 1.8% during the subsequent years. 2,[5][6][7] These figures are closely similar to ours despite the variation in the chosen upper age limit between the studies or whether patients with earlier stroke were included.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,15,16 The first-year mortality rates varied from 4.5% to 6.3%, 2,5-7 and the average rates were between 0.8% and 1.8% during the subsequent years. 2,[5][6][7] These figures are closely similar to ours despite the variation in the chosen upper age limit between the studies or whether patients with earlier stroke were included.…”
Section: Discussionmentioning
confidence: 99%
“…We found that younger patients were at relatively increased odds of stroke after ILI compared to older patients; for every decade younger age, the odds increased by almost 10%. While the absolute risk of stroke is greater in older adults, approximately 10–14% of all strokes occur in people 18–45 years old, with the incidence and prevalence of stroke in the young increasing 4, 28, 29, 30, 31, 32, 33, 34. This increasing prevalence, moreover, coupled with greater heterogeneity in stroke etiology within the younger age group than in the older stroke population, presents a unique and vulnerable patient population where risk reduction efforts are of increasing importance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed on ischemic stroke among the 15-45 years age group from India also reported a male preponderance [12][13][14][15] . In several studies, females outnumbered men among those under 30 [16][17][18] . The clinical spectrum of the young stroke patients in the present study is similar to other studies from India and abroad 12 .…”
Section: Discussionmentioning
confidence: 99%